Sequence comparison of six human microRNAs genes between tuberculosis patients and healthy individuals. Issue 4 (December 2015) - Amila, A.; Acosta, A.; Sarmiento, M.E.; Suraiya, Siti; Zafarina, Z.; Panneerchelvam, S.; Norazmi, M.N.
Abstract: Objective/Background: MicroRNAs (miRNAs) play an important role in diseases development. Therefore, human miRNAs may be able to inhibit the survival of Mycobacterium tuberculosis (Mtb) in the human host by targeting critical genes of the pathogen. Mutations within miRNAs can alter their target selection, thereby preventing them from inhibiting Mtb genes, thus increasing host susceptibility to the disease. Methods: This study was undertaken to investigate the genetic association of pulmonary tuberculosis (TB) with six human miRNAs genes, namely, hsa-miR-370, hsa-miR-520d, hsa-miR-154, hsa-miR-497, hsa-miR-758, and hsa-miR-593, which have been predicted to interact with Mtb genes. The objective of the study was to determine the possible sequence variation of selected miRNA genes that are potentially associated with the inhibition of critical Mtb genes in TB patients. Results: The study did not show differences in the sequences compared with healthy individuals without antecedents of TB. Conclusion: This result could have been influenced by the sample size and the selection of miRNA genes, which need to be addressed in future studies.